An investigation into the application of active networks to mobile computing environments - Chin, Kwan-Wu (Curtin University, 2000)
Telecommunication service providers have recently begun to offer ubiquitous access to packetised data. As a result, the Internet is not limited to computers that are physically connected but is also available to users that axe equipped with mobile devices. This ubiquitous access fuels the growth and the usage of the Internet even further, and thus the realisation of dynamic Internet. With the realisation of the dynamic Internet, increasing support is needed for Internet protocol (IP) and transmission control protocol (TCP) over wireless/mobile networks.Two areas of interest in this thesis are unicast and multicast routing in connectionless and connection-oriented networks. To address the problems of routing protocols in mobile computing environments, the active networks (ANs) paradigm is employed. ANs provide an alternative paradigm to solving network problems and comprise programmable network elements that allow enhancement of existing protocols and the execution of active protocols which run for the duration of the communication session.This thesis investigates the viability and advantages of ANs when applied to routing in mobile communications. Two new AN-based protocols, for IP and asynchronous transfer mode (ATM) networks, that address the problems of multicast routing with mobile group members are outlined. The Internet Engineering Task Force (IETF) mobile IP has been augmented with active programs in order to enhance its operation further. Also, a novel model for rerouting connections in ATM networks is presented.Results of extensive simulation studies comparing performances of conventional as well as some recently proposed protocols with those of AN-based protocols are presented. The results obtained from these simulation studies show that AN-based protocols have the following benefits: (i) efficient adaptation to mobility, (ii) reduced signaling overheads, (iii) high reuse of allocated network states, (iv) extensibility, (v) network topology independence, and (vi) scalability. The aforementioned points are crucial in mobile environments where states at routers (switches) are frequently updated due to mobility. It was shown that ANs provide the most benefits to protocols that maintain states within the network, for example connection-oriented and multicast protocols. AN-based protocols enable fast and efficient update of the states maintained at the routers/switches without incurring excessive signaling overheads. Moreover, part of a connection or multicast tree can be updated iteratively with the use of ANs, resulting only in modifications to routers (switches) that are affected by host migration. A model for deploying active programs that is coupled with the protocol operation is also demonstrated. Implementation of such a model eliminates the need for strategic positioning of active services.